Physical exercise and sedentary lifestyle: health consequences. - Monteiro, Diogo (2019)
Perhaps the greatest barriers for achieving major advances in public health in the twenty-first century result from the paralysis of the pandemic paradigm or from the widespread inability to envision alternative or new models of thought. Human movement represents a complex behavior that is influenced by personal motivation, health and mobility problems, genetic factors, and social and physical environments in which people live. These factors influence the propensity to engage in sedentary behaviors or in physical activity. However, the biological, social, and environmental pathways leading to sedentary behavior versus physical activity may be different. In addition, the health effects associated with sedentary behavior and physical activity may be the result of different biological mechanisms. Thus, our objective was to discuss the importance of physical exercise on health-related outcomes and the consequences of sedentary lifestyles. Research on sedentary behavior has been growing;however, the evidence for its determinants is relatively sparse. More studies are needed to obtain more conclusive results because it is fundamental to understand these complex relationships related to the practice and the acquisition of active and healthy lifestyles as opposed to a sedentary lifestyle.